STRATEGI LIFEPOD MEDIA DALAM MENINGKATKAN AUDIENCE ENGAGEMENT DI INSTAGRAM (Studi Kasus Pada Kanal “Ngomongin Film”) - Vahista, Salwa Lila; Subekti, Komarudin; Hikmah, Nur (Universitas Pakuan, 2025)
The term new media refers to types of media that utilize the internet and are based on online technologies. This form of media is characterized by its flexibility, interactive potential, and its ability to function both personally and publicly. As a result, new media has become a modern communication tool used by communicators to convey information to their audiences. Lifepod Media is a digital multiplatform media company established in 2019. It is active across various social media platforms, Instagram, Twitter, Facebook, TikTok, and YouTube are included. One of its Instagram segments, titled Ngomongin Film, focuses on reviewing Indonesian films. This segment utilizes the Instagram Live feature to discuss films that are either currently showing or upcoming in theaters. This study aims to explore and analyze the social media management strategies employed by Lifepod Media to increase audience engagement on the Ngomongin Film segment. The research applies the SOME model developed by Regina Luttrell, which consists of four key components: 1) Share, 2) Optimize, 3) Manage, and 4) Engage. The study is also grounded in the Uses and Gratification Theory. The findings indicate that the implementation of the SOME model has a significant and well-structured impact. Through this model, Lifepod Media successfully enhances audience engagement on the Ngomongin Film segment.